Determination of Irisin, Body Mass Index, and Other Biochemical Parameters in a Sample of Iraqi Type II Diabetic Patients - Takwa Al Koloob Ali Chachan; Huda Farhan; Shatha Hamed (Journal of Techniques)
Evidence suggests that Irisin, a peptide hormone, may play a role in lipid metabolism, insulin resistance, and obesity. On the other hand, its role in type 2 diabetic Mellitus [T2DM] in humans is uncertain. As a result, we investigated if irisin levels in T2DM patients were dysregulated and whether there was a link between serum irisin levels and anthropometric obesity indices and biochemical parameters. [T2DM patients] group [n = 90] and control groups [n = 90], males [n=81], females [n=99] were selected among 180 people. [43.17 ±11.13] years was the average age. ELISA was used to measure serum irisin levels. The mean serum Irisin level in the control group was considerably higher [P<0.01] than in the case group [6.9±1.3 vs. 5.8±1.2], respectively. The results showed that body mass index and irisin [P-value<0.001]. Irisin seems to have a significant negative connection [P-value<0.001] with body mass index, fasting blood sugar, glycated hemoglobin, insulin, and homeostasis model assessment of insulin resistance. There was also a substantial negative association between irisin, low-density lipoprotein, and triglyceride, but none with cholesterol or high-density lipoprotein. In conclusion, irisin appears to be involved in regulating glucose metabolism. In this investigation, circulating irisin concentrations were considerably lower in T2DM patients. These findings imply that higher plasma irisin levels in T2DM are linked to adiposity indices. As a result, irisin has the potential to be a novel therapeutic option in the field of obesity.